2018
DOI: 10.31234/osf.io/pvmex
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Danger of Interpreting Detection Differences between Image Categories

Abstract: Using breaking continuous flash suppression (b-CFS; a perceptual suppression technique), Gomes and colleagues (2018) showed that human observers have an advantage in detecting images of snakes (constituting an evolutionarily old threat) over birds. In their study, images of snakes and birds were filtered to contain either coarse-scale or fine-grained information. The preferential detection of snakes relied on coarse-scale (rather than fine-grained) information, which was taken as support for the existence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
2
19
1
Order By: Relevance
“…An Ill-Defined Concept Gayet et al (2019) claimed that the mechanism driving the faster snake detection observed in our results remains unclear, supporting their argument on the inherent visual differences observed between snake and bird images. The authors argued that the snakes' faster detection could be explained either by a processing advantage for threatening stimuli or by a processing advantage for threat-unrelated visual properties (e.g., perimeter-area ratio).…”
Section: "Threat-unrelated" Propertiessupporting
confidence: 85%
See 2 more Smart Citations
“…An Ill-Defined Concept Gayet et al (2019) claimed that the mechanism driving the faster snake detection observed in our results remains unclear, supporting their argument on the inherent visual differences observed between snake and bird images. The authors argued that the snakes' faster detection could be explained either by a processing advantage for threatening stimuli or by a processing advantage for threat-unrelated visual properties (e.g., perimeter-area ratio).…”
Section: "Threat-unrelated" Propertiessupporting
confidence: 85%
“…Recently Gayet et al (2019), using stimuli with no difference in the threat they represent (cars and bicycles), argued that some low-level features, such as the perimeter-area ratio of the images (which the authors called threat-unrelated properties), may have driven the detection advantages observed in our study . The results of Gayet et al (2019) evidenced that bicycles (a stimulus with an analogous perimeter-area ratio to that of snakes) were granted a faster access to visual awareness than cars (a stimulus with an analogous perimeter-area ratio to that of birds), both in the BSF and in the LSF conditions but not in the HSF condition. Based on these results, the authors then suggested that the detection differences between snakes and birds, observed in our study (Gomes et al, 2018), may have been driven by such a visual feature.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Specifically, the variability in the choice of spatial, temporal, and chromatic features of CFS masks is high across studies [27,36,38]. The critical importance of feature similarity between suppressed stimuli and CFS masks entails the risk of theoretically problematic confounds, especially when visually different stimuli are used in different experimental conditions [39]. For example, if a study finds that emotional pictures break suppression faster than neutral pictures, one might be inclined to conclude that emotional stimuli have preferred access to conscious-ness.…”
Section: The Bottom-up Effect Of Color Salience On Breakthrough Timesmentioning
confidence: 99%
“…One issue for studies using stimuli with intrinsic emotional value is that these stimuli differ not only in emotional meaning but also in terms of lower-level image properties, such as shape, texture, phase, amplitude, and spatial frequency spectrum. Indeed, several effects are better explained by differences in such low-level properties than by differences in emotional-motivational value (Gayet et al, 2019;Gray et al, 2013;Moors et al, 2019). For example, shorter suppression times for fearful faces in CFS reflect higher effective contrast rather than enhanced processing of threat (Hedger et al, 2015).…”
mentioning
confidence: 99%